The demographic determinants of inter-provincial migration declines in Canada: A decomposition analysis. (1st June 2021) - White, Nathaniel; Haan, Michael
Abstract: This article studies the link between observed demographic changes and Canadian inter-provincial migration declines. Alongside recent changes in age composition, educational attainment, marital trends, and immigration, Canadian internal migration has widely been in decline. In this context, our project investigates the demographic determinants of Canadian provincial migration and the correlation between Canada's socio-demographic shifts and the decline of inter-provincial migration. To do so, our analysis consists of two identical multivariate logistic regressions and an econometric decomposition using the data of the 1991 and 2016 Canadian Census Public Use Microdata Files. The dependent variable is inter-provincial migration, and the focal independent variables are age, educational attainment, marital status, immigrant status, and province of residence five years ago. By investigating how these determinants are associated with migration, we develop a greater understanding of how demographics predict inter-provincial migration in Canada, and how these demographics have changed and affected the overall decline in inter-provincial migration. In a broad sense, we examine the continuity of contemporary demographic trends in their relation to Canadian macro-economic human capital distribution. Through our investigation, we conclude that while compositional changes have some impact, it is a shift in the effects of these changes that largely explains the decline in Canadian inter-provincial migration.